DNA Fingerprinting Analysis of Oil Palm In Vitro Calli Using Simple Sequence Repeats (SSR) Markers - Arfan Nazhri Simamora; Diny Dinarti; Sudarsono Sudarsono; Sri Wening (Universitas Pattimura, 2022)
Propagating elite oil palm (Elaeis guineensis Jacq.) planting material through in vitro culture techniques requires more time and advanced technique. Early detection of culture stability would facilitate the process of culture selection and maintenance. This research aimed to analyze the DNA fingerprinting of explants and their calli. Calli consisted of embryogenic and non-embryonic calli, which had been subcultured three times. DNA of explants and calli isolated with DNeasy® Plant mini kit (Qiagen) and Genomic DNA Mini Kit (Plant) (Geneaid). DNA was amplified by SSR-PCR using 16 SSR markers, and can be bulked into two groups to save analysis cost.The result showed that 16 markers produced electropherograms that were identical between the explant and calli. Relatedness coefficient indicated that both compared explant and calli were genetically identical (r = 1). The markers used were quite informative with an average PIC number = 0.48 and can be used for DNA fingerprinting analysis of oil palm in vitro culture.